Personality Profile in Orthorexia Nervosa and Healthy Orthorexia - Roncero, María; Barrada, Juan Ramón; García-Soriano, Gemma; Guillén, Verónica (Frontiers in Psychology, 2021)
Little is known about orthorexia in both its pathological (orthorexia nervosa, OrNe) and adaptive (healthy orthorexia, HeOr) forms. To date, few studies have been carried out to analyze the personality profile associated with orthorexia, and the results have been contradictory. The aim of the present study was to explore the characteristic pathological personality traits associated with OrNe and HeOr. A total of 297 participants (Mage=30.8 years;94.6% women) from the general population completed the Teruel Orthorexia Scale (TOS) and Personality Inventory for DSM-5-Short Form (PID-5-SF) questionnaires. Results showed significant low-medium correlations between OrNe and the four personality factors (Negative Affectivity, Detachment, Disinhibition, and Psychoticism) (rs range[.08, .36]). In the regression analysis, the predictors of OrNe were Neuroticism and, to a lesser extent, Psychoticism. For HeOr, the associations were lower (rs range[–.13, .05]) and negative, except Psychoticism. Only the relationship with Disinhibition was statistically significant, although after controlling for OrNe, Negative Affectivity and Antagonism also became significant. In the regression analysis, the predictors of HeOr were Disinhibition (negative direction) and Psychoticism (positive direction). The findings show that OrNe is associated with a pathological personality pattern characterized by difficulty in regulating emotions and negative affect (Negative Affectivity), as well as eccentricity, feeling special, and holding beliefs outside the norm (Psychoticism). However, HeOr seems to be related to the tendency toward high responsibility, self-control, the ability to maintain the focus of attention (low Disinhibition), and Psychoticism. Future studies should confirm whether this combination is a key component underlying the development and maintenance of orthorexia.